Pemberian Sanksi (Hukuman) Terhadap Siswa Terlambat Masuk Sekolah Sebagai Upaya Pembentukan Karakter Disiplin - Ely Rahmawati; Ulfa Idatul Hasanah (Indonesian Publication Center, 2021)
In school activities, not a few students are late for school, it has even become a habit for students to be late. Students are late for school due to several factors, namely being late on purpose, unable to get up early, going to school with a tight time, waiting for friends, the distance between home and school that is far away, and so on. The impact of various reasons for students being late is the existence of deviant behavior that violates the rules / regulations that exist in school, both written and unwritten. Besides, it will also harm students, because they will miss their lessons in the first lesson. Besides that, this habit is not very good, if it continues like this it will make students have an undisciplined attitude which will be carried over to their big time. The research method uses literature studies by collecting data from previous studies using descriptive-analysis methods. The purpose of writing this journal is to discuss the importance of giving sanctions / penalties to students who are late entering school. This act is not an act of hazing or wanting to torture. However, this will have a deterrent effect on students from repeating their mistakes, besides that it will make students accustomed to going to school at the right time. This punishment is a form of learning in shaping the character of discipline in students.